ENHANCING STUDENTS SPEAKING SKILL THROUGH ACTING PLAY SCRIPTS (APS) TECHNIQUE - Herlina Herlina; Marleni Marleni; Mega Prasrihamni (Universitas PGRI Palembang, 2024)
During the process of learning to speak, students often encounter various challenges. Many students exhibit passivity in speaking lessons and lack confidence when speaking in front of the class due to limited vocabulary and a lack of conceptual understanding. The researcher aimed to determine whether the use of